Comparison of thoracic ultrasonography (TUS), clinical respiratory scoring (CRS), and blood analysis to evaluate respiratory dysfunction in transported calves - Luca L. van Dijk; Susanne Siegmann; Niamh L. Field; Katie Sugrue; Cornelis G. van Reenen; Eddie A.M. Bokkers; Gearoid Sayers; Muireann Conneely (PLoS ONE, 2026)
Mixing of calves during and after transport exposes them to large numbers of pathogens, increasing their risk of developing bovine respiratory disease after arrival. Identifying individual calves with respiratory disease is important to assess transport fitness and to facilitate timely treatment. This study compared three screening tests (thoracic ultrasound scores [TUS], clinical respiratory scores [CRS], and blood variables indicative of immune and inflammation status) for detecting respiratory disease in calves before and after transport to assess the degree of agreement in identifying respiratory dysfunction in transported calves. Thoracic ultrasound scores (0: healthy to 5: severe pneumonia; TUS of 4 and 5 were rare and reclassified as TUS 3 for analysis), CRS (0: healthy, 1: mild, 2: moderate, 3: severe), and blood variables (haemoglobin; red and white blood cell, neutrophil, lymphocyte, monocyte, basophil, and eosinophil counts; and neutrophil:lymphocyte ratio; serum-amyloid-A; total immunoglobulins; and immunoglobulins –A, -G, and –M) were compared in 65 calves at five time points; pre-transport (T1), on arrival (T2), 3 or 7 days post-arrival (T3; TUS and CRS only), and approximately ten (T4) and eighteen days (T5) post-arrival. Comparatively, TUS and CRS had different distributions between time points with TUS gradually increasing between T1 and T3 and declining thereafter, while CRS rapidly increased between T1 and T2, followed by a gradual decrease. Lymphocyte count was lower for a TUS of 3 than for a TUS of 1 or 2, serum-amyloid-A was higher for a TUS of 2 or 3 than for a TUS of 0, total immunoglobulins and immunoglobulin-G were lower for TUS of 3 than for a TUS of 2, and immunoglobulin-M was higher for a TUS of 1 or 2 than for a TUS of 0. Haemoglobin, WBC, and lymphocyte count were lower for CRS of 1 or 2 than for a CRS of 0. In conclusion, there was no agreement between TUS and CRS on the severities of individual scores. Though lymphocyte count was lower for moderate or severe CRS or TUS, no other blood variables showed a consistent pattern of change in relation to TUS or CRS.